Pengendalian Risiko Operasional Dalam Meningkatkan Kinerja Sekolah - Apri Chesa Fournanda; Irsyad, Irsyad; Merika Setiawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Operational risk control is a crucial element in school management, contributing to the smooth running of the teaching and learning process and pathe continuity ty of school activities. Uncontrolled operational risk can disrupt the confort, safety, and quality of from daily activities to achieve organizational strategies. Risk management must be based on risk identification, risk analysis, mitigation plan development, implementation, control, and evaluation to minimize negative impacts. Effective risk control, therefore, enables the creation of a conducive learning environment and supports improved school performance.